1996
DOI: 10.1074/jbc.271.49.31098
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation of Gsα and Inhibition of Bradykinin-induced Activation of the Cyclic AMP Pathway in A431 Cells by Epidermal Growth Factor Receptor

Abstract: An increasing amount of experimental data suggest that cross-talk exists between pathways involving tyrosine kinases and heterotrimeric G proteins. In a previous study, we demonstrated that bradykinin (BK) increases the intracellular accumulation of cAMP in the human epidermoid carcinoma cell line A431 by stimulating adenylate cyclase activity via a stimulatory G protein (G s␣ There is mounting evidence indicative of complex, probably cell-specific interactions between signaling pathways involving heterotrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Alternatively, activation of the EGF receptor by EGF could trigger the translocation of G␣s. It has been shown that G␣s is tyrosine phosphorylated by the EGF receptor in vitro and in response to EGF stimulation in vivo (Liebmann et al, 1996;Poppleton et al, 1996). Conceivably, this phosphorylation event might be related to the change in the subcellular localization of G␣s.…”
Section: Discussionmentioning
confidence: 98%
“…Alternatively, activation of the EGF receptor by EGF could trigger the translocation of G␣s. It has been shown that G␣s is tyrosine phosphorylated by the EGF receptor in vitro and in response to EGF stimulation in vivo (Liebmann et al, 1996;Poppleton et al, 1996). Conceivably, this phosphorylation event might be related to the change in the subcellular localization of G␣s.…”
Section: Discussionmentioning
confidence: 98%
“…EGFR tyrosine kinase activation triggers numerous downstream signaling pathways, including phosphorylation of G proteins, activation of phospholipase C, and downstream calcium and protein kinase C (PKC)-mediated cascades, and stimulation of the ERK pathway [52]. Purified EGFR can phosphorylate G sa in vitro [53] and in vivo [54] and directly stimulate of adenylyl cyclase; at the same time, it prevents G sa activation by G protein-coupled receptors, such as the bradykinin receptor, and reduces cAMP accumulation [54]. An increase in intracellular Ca 2+ , such as occurs following EGFR activation, can stimulate cAMP phosphodiesterases, inhibit adenylyl cyclases, and inhibit vasopressin-induced renal accumulation of cAMP [55].…”
Section: Discussionmentioning
confidence: 99%
“…Among the PTX-insensitive G proteins expressed in SW-480 cells, G 12/13 do not stimulate phosphatidylinositol hydrolysis (36) and may be excluded from linking the bradykinin receptor to phospholipase C␤. The bradykinin receptor appears to be capable of interacting with multiple G proteins, including also G s (23,37). If the effect of bradykinin on MAPK is triggered by ␤␥-complexes released from a G s protein as demonstrated for the ␤-adrenergic receptor (9), it might be expected that permanent activation of G s in the presence of CTX simulates or potentiates the BK action on MAPK.…”
Section: Discussionmentioning
confidence: 99%